Metaphysical Order. Suárez’s Theory of Real Relation (Doctor Virtualis, 2024)
It is commonly known that the notion of relation is one of the theoretical pillars of the metaphysical and theological doctrine of many medieval and modern scholastic authors, determining their cosmological world view. This essay aims to reconstruct the notion of real relation in Francisco Suárez's thought, exploring its internal articulation in lower concepts and addressing some problematic cores peculiar to the scholastic debate. The first section of the paper considers the extension of the concept of real relations, drawing the fundamental distinction between categorical and transcendental relations: while the former are accidents that must fulfil three conditions in order to exist (the existence of a subject, a foundation and a term), the latter are not accidents and are thus part of the essence of the thing they refer to. The second part focuses on the intension of the concept of real relation, concluding by defining it as a real reference based on the first element of the relation (the foundation) and directed towards the second (the term) as something else. Finally, the last section of the essay addresses the problem of the nature of the distinction between the relation and its foundation. After examining some eminent authors’ position, namely Thomas Aquinas, Duns Scotus, Durandus of Saint-Pourçain and Pedro da Fonseca, Suárez assumes the Nominalist position which reduces the ontological status of the relation to that of its foundation. In this regard, Suárez's doctrine differs from Ockham's only by adding the thesis of the distinction of reason between the relation and its foundation, a position unacceptable for Nominalists.
Keywords: Francisco Suárez; Real Relation; Foundatio; Term; Nominalist Reduction